Analysis of Human Resource Planning in Facing Challenges in The Digital Era at State Vocational School 2 Gunungsitoli, Gunungsitoli City - Jepi Masa Mendrofa; Yamolala Zega; Heniwati Gulo; Robin Markus Putra Waruwu (PT. Maju Malaqbi Makkarana, 2025)
This study aims to analyze human resource (HR) management planning, identify obstacles, and formulate efforts to support the digitalization of school management. The study used a qualitative descriptive approach with in-depth interviews, observation, and documentation techniques with the principal, vice principal, teachers, and administrative staff. The results showed that HR planning at SMK Negeri 2 Gunungsitoli was carried out through three main steps: (1) needs analysis and preparation of technology-based teacher formation, (2) competency mapping and identification of information and communication technology (ICT) training needs, and (3) empowerment of teachers and staff through workshops, mentoring, and discussion forums. Obstacles faced included limited digital literacy among teachers and staff, unequal network access, and resistance to changes in technology-based learning methods. Efforts made by the school included providing digital literacy training, optimizing available devices and networks, utilizing offline learning applications, and creating a work culture that is adaptive to innovation. This study concluded that targeted HR planning, infrastructure support, and continuous competency development are important factors in realizing effective digital transformation in schools. These findings are expected to be useful for SMK Negeri 2 Gunungsitoli, other educational institutions, and further researchers in developing digitalization strategies for school management.